Synthesis of polyurethane acrylate hybrids containing fluorine and siloxane by the sol–gel method for UV-curable coatings - KARATAŞ, SEVİM (My University, 2022)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.In this study, five different UV-curable polyurethane acrylate (PUA) resins (B, H:20, H:40, P:10/H:20, and P:20/H:40) were synthesized using different amounts of polyols [(2,2-bis(4-β-hydroxyethoxy) phenyl 6F propane (HEPFA); polydimethylsiloxane (PDMS); propylene glycol) which reacted with isophorone diisocyanate (IPDI) and end-capped with 2-hydroxyethyl methacrylate (HEMA). Then, a series of UV-curable PUA formulations and their nano-hybrids (B/S10-30, H20/S10-S30, H40/S10-S30, P10:H20/S10-S30, P20:H40/S10-S30) were prepared by the sol–gel method using different amounts of sol–gel solutions. The obtained formulations were cured with UV rays. The effects of PDMS, HEPFA and sol–gel content on the physical, thermal and mechanical properties of the UV-curable PUA coatings were investigated. When the HEPFA, PDMS and sol–gel content were increased in the urethane base formulation (B), the gloss increased from 98° to 117°, 133° and 137° for B, H40, P20:H40 and P20:H40/S30, respectively. TGA analysis showed that the decomposition temperatures shifted significantly upward with increasing amounts of HEPFA, PDMS and the sol–gel precursor. The water absorption of the hybrids decreased from 4.7 wt% (B) to 2.5 wt% (P20:H40/S30). The nano-hybrid coatings exhibited higher contact angle values for deionized water/ethylene glycol compared to the pure PUAs, ranging from 52°/48° (B) to 78°/76° (P20:H40/S30). The SEM analysis showed that the nano-silica particles were scattered in the polymer matrix without serious agglomeration when 30 wt% of sol–gel solution was added to B, H40 and P20:H40. These results indicate that the overall properties of the PUAs and their hybrids were improved and that they could potentially be used as coatings in practical applications.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; PHYSICS; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; PHYSICS, CONDENSED MATTER; Genel Kimya; Fizik Bilimleri; Yoğun Madde Fiziği; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Condensed Matter Physics; Polymers and Plastics; Materials Chemistry; Coating; Hybrid materials; Polyurethane acrylate; Sol–gel technique; UV-curing; Polyurethane acrylate; Coating; UV-curing; Sol–gel technique; Hybrid materials